The dynamics of speed indices analysis among Russian ice-skaters at 500 meters distance depending on age and qualification - Morozova, E. A. (The Russian Journal of Physical Education and Sport, 2017)
Modern tendencies in the sphere of speed skating are mainly connected with the speed of running increase along the distance and, as a result, with sports results improvement. Therefore, the specialists in speed skating face the following problems: training process optimization and rationalization, the search for new means, methods and methodologies of the training process organization and training sportsmen in accordance with modern tendencies of speed skating development. Materials: The aim of this research work is in differences revelation and the factors determination, which condition them, in the results of Russian ice skaters of different age and qualifications. This article presents the factorial analysis of the results at 500 meters distance among ice-skaters at the World Championship according to the separate distances, Russia Championship according to the separate distances, the Championship of Russia among juniors, and young people of all ages (season 2015). Research methods. The information for the research was received as a result of video of running and the official score sheets analysis. Statistical data handling was fulfilled with the help of the following programs: Microsoft Excel (2010) and STATGRAPHICS Centurion. Results. At the first stage of the research it was stated that common planned schedule includes the competitions of Russia Championship and the Championship of Russia in 5 age groups and a tight schedule of elimination competitions. Ice-skaters of the junior age group have considerable differences in the level of physical and technical readiness and in general are characterized by a low level of sports qualification (II sports category and lower). The next step belongs to the mid age group - 30% of boys exceed the set norms of Candidate Master of Sports. However, there is no further sportsmanship improvement - the results of Candidate Master of Sports among senior age group and juniors is more than 80%. Only 19% of juniors were able to fulfill the normative of the master of sports of Russia- all were the participants of the Championship of Russia. At the second stage of the research, with the help of Principal Component Analysis, it was stated that 99,13% of the full sampling variance are conditioned by two components: a) difference in speed of movement along the distance, connected with biological, physiological and functional differences of ice-skaters of different age groups; b) technical-tactical mastery while passing the turns, by the ability to gain maximum speed of running at the given parts of the distance. Conclusion. Master of sports level achievement is closely connected with the ability to increase speed while running along the turn. During technical-tactical mastery improvement ice-skaters should pay attention to the technique of passing as the most favorable part for maximum speed development.